Friction and wear behavior of Fe2AlB2 nanolaminates against GCr15 steel counterpart. Issue 12 (15th August 2020) - Song, Guangping; Sun, Dongdong; He, Xiaodong; Qi, Xinxin; Zheng, Yongting; Gao, Jin; Yin, Hang; Bai, Yuelei
Abstract: The dependence of the friction and wear behavior of MAB-phase Fe2 AlB2 against GCr15 steel counterpart on the sliding speed (0.8–6.4 m/s) and normal force (20–60 N) is investigated. The friction coefficient (0.3–0.7) decreases with increasing sliding speed and normal force, however, with some abnormalities for low sliding speeds of 0.8–1.6 m/s in the latter case. In contrast, overall increasing wear rates ((0.5–2.5) × 10 -5 mm 3 /(N·m)) are observed, with significantly high values at 0.8 m/s and 40–60 N. Surface oxidation is identified due to the high temperature. At 0.8–1.6 m/s, the surface tongue patterns and material migration are both indicative of adhesive wear, with the contribution of fatigue wear becoming more significant for sliding speeds of over 3.2 m/s. At 6.4 m/s and 40 N, the wear changes from deformation-controlled by shallow spalling to fracture-controlled by deep failure.